Housing Demand During the Boom: The Role of Expectations and Credit Constraints - Landvoigt, Tim (Review of Financial Studies, 2017)
I use a life-cycle model of housing demand to infer expectations about house prices and home equity requirements for the housing boom of the 2000s from observed household choices. Expectations and credit constraints are separately identified from the intensive and extensive margins of housing demand. The main results are that (1) expected price growth was close to average long-run growth, (2) home equity requirements were lax initially, but tightened after the bust, and (3) subjective uncertainty about future price growth was large. Given the option to default on mortgage debt, greater price uncertainty leads to higher optimal household leverage.